PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING ( CTL ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 12 PANGKALAN JAMBI KECAMATAN BUKIT BATU - Zamharil Zamharil; Syahrilfuddin Syahrilfuddin; Lazim Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low learning outcomes IPS Grade IV SD Negeri 12 Pangkalan Jambi of learning IPS as expected has not been achieved 75% of the provisions. It is evident from the number of students who have not yet reached complete learn while the minimum standard criteria (KKM) set the school is 65. This is confirmed from the 19 students only five people (27%) of students who reached the KKM. And 14 (73%) of people do not reach KKM with an average value of 51.58, One of the learning that is expected to achieve this is by the application of learning models Contextual Teaching and Learning (CTL). Increased activity of the teacher in the learning process in the first cycle of the first meeting of 57.14% with enough categories, and the second meeting of 67.85% with both categories. Then the increase in cycle II to the first meeting of 78.57% with a good category, and the second meeting of 85.71% premises nkategori very good. Increased activity of students in the first cycle of meeting pertama57,14% with less category, and the second meeting of 64.28% with enough category. Then increased again in the second cycle of meetings pertama7,14% with enough categories and the second meeting of 78.57% with a good category and resulting increases in social studies students from a base score to the first cycle ie from an average of 51.58 into 66.32 with an increase of 14.74% and an increase learning outcomes of the first cycle to the second cycle of an average of 66.32 into 76.58 with an increase of 25%.Key words: Implementation Approach Contextual Teaching And Learning (CTL),, Learning Outcomes IPS.